Strategi Optimalisasi Akun @Thrift.Bylia Dalam Meningkatkan Penjualan Pakaian Melalui Media Instagram - Nadia Nadia; Achmad Syarifudin; Sri Hertimi (Journal of Innovative and Creativity, 2026)
The phenomenon of thrifting, or the sale of used clothing that is still wearable, is becoming increasingly popular among the public, especially the younger generation, as evidenced by the increase in the number of followers of the Instagram account @thrift.bylia, which has reached thousands of followers since the account was created. This study aims to analyze the optimalization strategy of the Instagram account @thrift.bylia as a promotional medium to increase online sales of thrift clothing. The research method used is a qualitative approach with a descriptive research type, where the research data is obtained through direct observation, interviews, and documentation. The results of this study found that the strategy applied by @thrift.bylia in optimizing Instagram relies on the integration of planned content management and the strengthening of visual identity. It was also found that customer response to @thrift.bylia's promotional strategy showed a very positive trend, as indicated by high levels of consumer trust and loyalty. Thus, this study confirms that the success of @thrift.bylia's sales increase is not only determined by product quality but also by the synergy of planned and consistent digital marketing communication strategies